METHODS OF ASSESSING THE QUALITY OF PROFESSIONAL TRAINING BASED ON DIGITAL PLATFORMS (Innovative professional education, 2025)
The digital transformation of vocational education requires new approaches to assessing the quality of skilled workers’ training. The article analyses modern assessment methods based on digital vocational training platforms, including automated monitoring systems, learning analytics and adaptive assessment technologies. Particular attention is paid to personalised feedback, digital footprint analysis and the use of artificial intelligence to improve the educational process. Recommendations for the effective implementation of digital platforms to improve the quality of professional training are offered.
Keywords: digital technologies, vocational education, quality assessment, digital platforms, vocational training